2D-ERT data measured in June 2023 and June 2024 in the Lower Havel Inner Delta near Lake Gülpe, Brandenburg (Germany) - Pohle, Marco; Birnstengel, Susann; Werban, Ulrike (In: Köhler, Anne; Pohle, Marco; Bauckholt, Matteo; Birnstengel, Susann; Kaniecki, Marie; Schneider, Birgit; Werban, Ulrike; Zielhofer, Christoph (2025): Geophysical, Sedimentological and Geochemical Data from the Lower Havel Inner Delta (Gülpe Island), Brandenburg (Germany) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.983208, 2025)
The Electrical Resistivity Tomography (ERT) data were acquired by using a PC controlled DC resistivity meter system (RESECS, Geoserve, Kiel, Germany). In total, we measured four ERT transects. Two transects in June 2023, where transect 1 had a total length of 259 m with an electrode spacing of 0.5 m and transect 2 had a total length of 223 m with an electrode spacing of 1 m. The measurements in 2023 were carried out under extreme dry conditions. Two further transects were measured in June 2024 with an electrode spacing of 1m, transect 3 with a total length of 207 m and transect 4 with a total length of 239 m. We applied wenner alpha and dipol-dipol configuration. The coordinates and the height of the electrodes were measured with a D-GPS (2023: TOPCON HiPer II / 2024: Leica GPS1200).
Keywords: Brandenburg; Electrical Resistivity Tomography; ERT; floodplain; Lake Gülpe; Near surface geophysics